1972
DOI: 10.3171/jns.1972.36.5.0652
|View full text |Cite
|
Sign up to set email alerts
|

Ganglioneuroma-paraganglioma of the intradural filum terminale

Abstract: ✓ A rare ganglioneuroma-paraganglioma of the filum terminale is reported, and the histological, histochemical, and ultrastructural characteristics of the lesion described. Classification was resolved by the ultrastructure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0
1

Year Published

1974
1974
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(56 citation statements)
references
References 16 publications
0
55
0
1
Order By: Relevance
“…Most authors consider GPs to be variants of gastrointestinal tract paragangliomas (18). Paragangliomas may differentiate to other neuroectodermal elements, including neurons and Schwann cells (19). Further evidence of potential for divergent differentiation of neoplastic neuroendocrine cells includes the observation that, when stimulated by nerve growth factor, cell cultures from carcinoid tumor or small cell carcinoma differentiate toward neurons (20).…”
Section: Discussionmentioning
confidence: 99%
“…Most authors consider GPs to be variants of gastrointestinal tract paragangliomas (18). Paragangliomas may differentiate to other neuroectodermal elements, including neurons and Schwann cells (19). Further evidence of potential for divergent differentiation of neoplastic neuroendocrine cells includes the observation that, when stimulated by nerve growth factor, cell cultures from carcinoid tumor or small cell carcinoma differentiate toward neurons (20).…”
Section: Discussionmentioning
confidence: 99%
“…PGs were reported for the first time by Miller and Torack in 1970 and called secretory ependymomas (15). In 1972 Lerman et al reported a similar case and named it paraganglioma (13). Spinal paragangliomas comprise 3-4% of all spinal tumors, and about 200 cases of cauda equina PG have been reported in the literature (1,5,29,30).…”
Section: Introductionmentioning
confidence: 97%
“…PG derives from the embryonic sympathetic and parasympathetic nervous system (13,15,20,28). PGs of the central nervous system have been reported in a few case series, particularly in the cauda equina (24) and spinal nerve roots (13,15). PGs were reported for the first time by Miller and Torack in 1970 and called secretory ependymomas (15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lerman and Kaplan 11 were the first to coin the term paraganglioma of the cauda equina in 1972. Lumbar paragangliomas are usually located in the cauda equina and filum terminale region.…”
Section: Jossmentioning
confidence: 99%